2013
DOI: 10.1159/000353245
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in Patients with Thiamine Deficiency after Roux-en-Y Gastric Bypass Surgery

Abstract: Background/Aims: Roux-en-Y gastric bypass surgery is the most common bariatric surgery worldwide. We have described thiamine deficiency in patients with small intestinal bacterial overgrowth after gastric bypass. We hypothesized that symptoms of thiamine deficiency are common after gastric bypass. The aims of this study were to examine the prevalence of and treatment of symptoms of thiamine deficiency after gastric bypass. Methods: This is a prospective study performed in a large urban, community hospital. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…Chaves et al 46 reported that encephalopathy due to thiamin deficiency occurred in only 0.18% (of 1663 patients) after BPD 39 . More recently, Shah et al 47 prospectively reported symptomatic thiamin deficiency in 18% of post‐RYGB patients. The risk for thiamin deficiency may be more striking in those with alcohol abuse after bariatric surgery.…”
Section: Specific Micronutrient Deficienciesmentioning
confidence: 99%
“…Chaves et al 46 reported that encephalopathy due to thiamin deficiency occurred in only 0.18% (of 1663 patients) after BPD 39 . More recently, Shah et al 47 prospectively reported symptomatic thiamin deficiency in 18% of post‐RYGB patients. The risk for thiamin deficiency may be more striking in those with alcohol abuse after bariatric surgery.…”
Section: Specific Micronutrient Deficienciesmentioning
confidence: 99%
“…Symptoms of nausea, vomiting and dysphagia have been observed in a significant proportion of individuals with thiamine deficiency[22,23]. Thiamine deficiency is a known complication of bariatric surgery, and in a previous prospective study we found an 18% prevalence of thiamine deficiency in patients after gastric bypass surgery[24]. In parallel work, Van Rutte et al[25] reported a 5.5% prevalence of thiamine deficiency one year after VSG, while Saif et al[26] reported thiamine deficiency in 14.3% and 30.8% of patients 3 years and then 5 years after VSG.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroenterolic causes of TD include slow gastric emptying, nausea, vomiting, jejunal dilatation, and/or megacolon 54 . In addition, constipation may also be a sign and symptom of TD 73 . Small‐bowel bacterial overgrowth (SBBO) can also result in low thiamin levels 74 .…”
Section: Deficiency: Signs and Symptomsmentioning
confidence: 99%